2016
DOI: 10.1142/s0217984916501578
|View full text |Cite
|
Sign up to set email alerts
|

Citrate complexing sol–gel process of lead-free (K,Na)NbO3 ferroelectric films

Abstract: The citrate complexing sol–gel process to fabricate lead-free (K,[Formula: see text]Na)NbO3 ferroelectric thin films was studied. Soluble niobium source of niobium–citric acid (Nb–CA) solution was utilized as a raw material to synthesize (K,[Formula: see text]Na)NbO3 thin films, by pyrolyzing at 450–550[Formula: see text]C and annealing at 650[Formula: see text]C. The film pyrolyzed at 450[Formula: see text]C shows poor crystallization with porous morphology, whereas the film pyrolyzed at 550[Formula: see text… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…In the left side micrograph (Figure A), the surface of the post‐heated gel shows the clear presence of pores ascribable to the release of CO 2 gas during the annealing process. The CO 2 evolution is a consequence of the thermal decomposition of the complex oxalates formed through the gelation, as it was already observed by Yao et al and further confirmed by Rani and coauthors . Upon compaction and subsequent annealing at 500 °C, the surface morphology of the final pellet changes with respect to the un‐treated powders.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…In the left side micrograph (Figure A), the surface of the post‐heated gel shows the clear presence of pores ascribable to the release of CO 2 gas during the annealing process. The CO 2 evolution is a consequence of the thermal decomposition of the complex oxalates formed through the gelation, as it was already observed by Yao et al and further confirmed by Rani and coauthors . Upon compaction and subsequent annealing at 500 °C, the surface morphology of the final pellet changes with respect to the un‐treated powders.…”
Section: Resultssupporting
confidence: 66%
“…The CO 2 evolution is a consequence of the thermal decomposition of the complex oxalates formed through the gelation, as it was already observed by Yao et al and further confirmed by Rani and coauthors. [27,48] Upon compaction and subsequent annealing at 500 C, the surface morphology of the final pellet changes with respect to the un-treated powders. As a consequence of the annealing treatment and uniaxial pressure, evidenced in Figure 3B, the pores definitely disappeared together with a significant crystal growth and the presence of small particles, in agreement with other synthetic procedures.…”
Section: Synthesis and Structural Characterization Of The Knn Systemmentioning
confidence: 99%
“…The gas released during the calcination at 450 C, generated a significant porosity degree with pore dimensions of 10-20 nm. However, the ferroelectric properties were improved only when the system was heated upon 550 C. [97] Dielectric properties could be modulated in KNN system by doping with amphoteric elements. [98] Yttrium, depending on the concentration, can replace ions in the A-or B-site.…”
Section: Knn-mn/knn-tamentioning
confidence: 99%
“…Chemical solution deposition (CSD) of the KNN-based thin films can be divided according to the alkali metal starting compounds such as acetate based (Kupec et al 2012;Wang et al 2009;Wiegand et al 2013;Yan et al 2010), alkoxide based (mainly ethoxides) (Kang et al 2011;Nakashima et al 2007;Tanaka et al 2007;Yu et al 2013), and only in rare studies non-alcohol niobium salt based (Lu et al 2014;Yao and Zhu 2016). The advantage of the alkali acetate-based over the alkoxidebased method is in the favored crystallization of the single perovskite phase films on platinized silicon substrates at 600-680 C (Čakare-Samardžija et al 2008).…”
Section: Chemical Solution Deposition Of Knn-based Filmsmentioning
confidence: 99%